Antibacterial bone cement modified by long-chain nitrofuran methacrylate using liquid-phase modification strategy - Lin, Hao; Gao, Zhe; Han, Lu-Yang; Chu, Jian-Jun; Xu, Yang; Shen, Dian-Hong (Frontiers in Materials, 2024)
A novel acrylic monomer containing a nitrofuran motif, referred to as long-chain nitrofuran methacrylate (LNFMA), is reported. In comparison to the previously reported nitrofuran methacrylate (NFMA), LNFMA has a longer side chain, and when incorporated into bone cement, the resulting LNFMA bone cement exhibits improved mechanical strength. At the same concentration, NFMA-5% cement has only 21.6 ± 1.3 MPa, while LNFMA-5% cement has a compressive strength of 42.64 ± 0.94 MPa. LNFMA bone cements exhibit antimicrobial activity against Staphylococcus aureus, with LNFMA-30% cement reaching 57.38 ± 5.53%.. Moreover, LNFMA cement demonstrates excellent biocompatibility both in vitro and in vivo. The results showed that LNFMA monomer had optimized mechanical strength compared with previously reported NFMA monomers, and LNFMA bone cement had good antibacterial activity and biocompatibility.